ETIKA DAN PENGGUNAAN TEKNOLOGI INFORMASI: FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI MAHASISWA AKUNTANSI UNTUK MELAKUKAN PEMBAJAKAN PERANGKAT LUNAK - Dwi Prihatini (STMIK PONTIANAK, 2011)
Abstracts: Software Piracy has become a serious global problem, not only in the industrial world but also happened in the world of education. This research conducted to investigate what kind of factors causing software piracy intention in academic institution. Former research used the attitude variable, gender, majors, student’s family income, ownership of computer, and institutional monitoring and clarification. This research added the education level variable with the 79 responses and found that attitude variable, gender, the level of education, and ownership of computer influence the student intention to do the software piracy.Keyword: software piracy, student’s attitude, academic institution